Media representations of crimes in close relationships: Qualitative analysis of narratives in a television broadcast - De Gregorio, Eugenio; Mongai, Camilla; Tiberio, Lorenza (Frontiers in Psychology, 2022)
Recent years have seen increased media attention paid to crimes committed against women by partners or former partners has grown. Crime, especially violent crime, dominates the news and the mass media. In this sense, criminology” impacts publicly the collective representation of crime. The study was motivated by the interest to understand what representations are conveyed by television broadcasts and how closely related they are to criminological theories and literature on the subject. The objective of the proposed qualitative research is to examine the media representations proposed in thematic television broadcasts, as well as the narrative profiles relating to the victims, perpetrators of the crimes and their relationships, as described in the news and by a multiplicity of roles associated with them based on kinship, friendship or professional role.